The effect of diosgenin and condensed tannin in Musa x paradisiaca flower on rats milk composition and growth rate of suckling pups - Ngah, Nurziana; Mahmood, Azizah; Omar, Muhammad Nor (2012)
The presence of secondary compounds has been recognized to have a profound effect upon both the nutritive and feeding value of foods. These effects are beneficial in some instances. In this study, a steroid saponin known as diosgenin and condensed tannin from Musa x paradisiaca flower were evaluated for its potential efficacy in accelerating growth rate of Sprague Dawley suckling pups. Nutrients composition of milk collected from the nursing rats using a modified mechanical device after an injection of oxytoxin were also determined. Pups growth rates (g/day) for all treatments groups were measured as the slope of the regression of y = pup weight versus x = day of lactation. Pups growth rate was significantly improved for the groups treated with the aqueous and diosgenin extract in which the equation are y = 1.871x – 0.271 and y = 1.712x + 2.059, compared to negative control, metochlopramide and tannin which are y = 1.434x + 2.221, y = 1.349x + 3.602 and y = 1.221x + 5.397, respectively. The proximate value in dry weight basis of milk showed that it contains of moisture, fat, protein, ash and carbohydrate of 4.179 – 5.739 %, 36.248 – 45.563 %, 30.323 – 34.293 %, 6.52 - 8.451 % and 10.475 – 16.751 %, respectively. High protein content measured in milk of diosgenin extract group suggests a possible effect of the extract in improving growth rate of the suckling pups.